Theoretical characterization of the temperature dependence of the contact mechanical properties of the particulate-reinforced ultra-high temperature ceramic matrix composites in Hertzian contact. (April 2021) - Wang, Ruzhuan; Wang, Shu; Li, Dingyu; Xing, An; Zhang, Jun; Li, Weiguo; Zhang, Chuanzeng
Highlights: Temperature dependence of contact mechanical properties is characterized by theory. The theoretical models are expressed in terms of some basic material properties. Nature and underlying physical control mechanisms at high temperatures are revealed. Excellent agreements are obtained between model calculations and measurements. Abstract: The novel theoretical models for the temperature dependence of the contact mechanical properties of the particulate composites in Hertzian contact are proposed in this paper, based on an assumption of the temperature-independent constant energy storage capacity for a specific brittle particulate composite, associating with the material yielding, and the theory of Hertzian contact. The yield stress, critical loads for the onset of the brittle and quasi-plastic damage modes, indentation strength, and the more commonly used fracture strength of the composites are expressed in terms of the basic material properties—the temperature-dependent Young's modulus and specific heat capacity, and the critical flaw size. The models enable the priori and quantitative predictions of the contact damage behavior of the composites during the whole process of the Hertzian contact. The models are validated by comparing against the experimental measurements of the temperature-dependent contact mechanical properties of the particulate-reinforced ultra-high temperature ceramic matrix composites in the temperature range of 25 ∼ 800 °C, which were found probably to be the only reported experimental studies of the particulate composites. The temperature dependence of the contact damage behavior of the composites is revealed to be mainly governed by the temperature-dependent Young's modulus and specific heat capacity, and the change of the flaw size above a certain temperature point. The models provide additional adequate methods for the determination of the nature and the underlying physical control mechanisms of the damage behavior of the composites at high temperatures.